ECO-ANXIETY AND PRO-ENVIRONMENTAL BEHAVIOR: A DOUBLE-EDGED SWORD? - Julian Amriwijaya; Sunggoro Trirahardjo (INJOSEDU: International Journal of Social and Education, 2025)
The increasingly apparent phenomenon of global climate change has given rise to significant psychological responses among the public, one of which is eco-anxiety. This study aims to examine the relationship between eco-anxiety and pro-environmental behavior through a literature review approach. This study analyzes various empirical and theoretical findings that address whether eco-anxiety acts as a driver of ecological action or inhibits it due to its excessive emotional impact. The results indicate that eco-anxiety has a dual role: on the one hand, it can encourage individuals to engage in concrete actions for environmental sustainability; on the other hand, if not managed properly, this anxiety can lead to feelings of hopelessness and inactivity. This study concludes that constructively managing eco-anxiety is crucial to transform it into positive motivation supporting environmentally friendly behavior. Furthermore, educational and psychological interventions are needed that can frame ecological anxiety as a form of concern, rather than a paralyzing fear.